Effect of BOPO, CAR, and NPF on Mudharabah Deposits (Study on Islamic Banking Listed on the Stock Exchange 2016-2018 Period) - Herby Ernanto; Sigit Hermawan (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the effect of BOPO, CAR, and NPF on Mudharabah Deposits in Islamic Banking Companies Listed on the IDX for the 2016-2018 period. The sampling method used is purposive sampling method. The number of companies that were sampled in this study were 10 Islamic Banking Companies Listed on the IDX for the 2016-2018 period. The data used is secondary data. The data analysis method used in this research is Multiple Linear Regression. The results of this study indicate that BOPO has an effect on Mudharabah Deposits in Islamic Banking Companies for the 2016-2018 period, CAR has an effect on Mudharabah Deposits in Islamic Banking Companies for the 2016-2018 period, and NPF has an effect on Mudharabah Deposits in Islamic Banking Companies for the 2016-2018 period.